(untitled) (International Journal of Innovative Technologies in Economy, 2023)
Pricing for the service of using freight cars using data from past periods reduces the income of JSC «Ukrzaliznytsia». The transition to the market price of the service will allow the company to increase demand and income from the use of freight cars.